Verkhneudinsky Branch of the Russian-Asian Bank in Credit and Financial Market of Western Transbaikalia in 1911-1914 - A. M. Plekhanova; A. A. Shirapov (Научный диалог, 2020)
The analysis of the activities of the Verkhneudinsky branch of the Russian-Asian Bank (until 1910 - Russian-Chinese) on the credit and financial market of Western Transbaikalia in 1911-1914 is presented, its influence on the development of trade and industry of the region is determined. Based on the reporting and office records stored in the State Archive of the Republic of Buryatia and the Russian State Historical Archive, the dynamics of the active and passive operations of the banking branch in the context of the all-Russian industrial expansion in 1909-1913 was analyzed. It was established that the Verkhneudinsky branch of the bank espouse cautious financial policy, issuing loans to its customers at inflated interest rates. It is proved that, despite the favorable situation in the country's economy during the indicated period, the credit and financial institution in Verkhneudinsk has largely lost its dominant position in the banking services market of Western Transbaikalia. According to the authors, this circumstance was the result of a sharp increase in competition in connection with the emergence in the fairly small financial and credit market of the region of two new banking institutions - the Verkhneudinsky and Kyakhtinsky mutual credit societies.